Activity Level, Body Mass Index, and Postural Habits Awareness in Adolescents - Nani, Desiyani; Saryono, Saryono; Pratiwi, Hikmi Muharromah (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2024)
Background: Early adolescence is a period of growth and development marked by the onset of puberty, where important changes occur in psychological development and social roles. Excessive internet use, especially in adolescents at this time, causes health problems such as postural disorders, sedentary lifestyles, and unbalanced nutrition. Objective: This study was planned to investigate the level of activity, body mass index and habits and awareness of posture in early adolescents. Method: Measurements of body weight, height were carried out, participants filled out a questionnaire on knowledge of posture, knowledge of ergonomics and a questionnaire on postural habits awareness. Results: Participants were 33 children aged 11-17 years. Knowledge of posture at a high level was 17 adolescents (51.5%). Knowledge of musculoskeletal disorders at a moderate level was 26 adolescents (78.78%). Posture habits were mostly at a good level as many as 29 adolescents (87.9%). Conclusion: The level of activity of adolescents was mostly at a moderate level and nutritional status based on BMI was mostly in the thin category. Knowledge of posture, ergonomics and habits and awareness of posture is at medium and high levels. Indicating adequate information has been obtained by participants.